Faktor yang Mempengaruhi Performa dari Kinerja Bisnis di Negara Berkembang dari Sudut Pandang Owner – Manager pada Usaha Laundry - Alexander, Jonathan; Hosen, Chandra (Business Management Journal, 2025)
The rapid growth of MSMEs, particularly in Indonesia's laundry sector, presents challenges for business owners to improve performance amidst intense competition. This quantitative research involved 83 respondents, consisting of laundry business owners or managers in Jakarta, selected through purposive sampling. Data measurement was conducted using a 5-point Likert scale, and data processing employed the Partial Least Square-Structural Equation Modeling (PLS-SEM) method via SmartPLS version 4.1.0 software. This study aims to analyze the influence of Entrepreneurial Orientation, Growth Orientation, and Market Orientation on Business Performance, with Brand Orientation as a mediating variable. The results indicate that Market Orientation significantly affects Business Performance, while Entrepreneurial Orientation and Growth Orientation do not. Additionally, Brand Orientation does not mediate the relationships between the variables significantly. These findings highlight the critical role of market orientation and operational efficiency in improving MSME performance in the laundry sector. Thus, prioritizing customer needs and market-based strategies becomes essential to maintain competitiveness in the industry.